(untitled) (Bangladesh Journal of Agricultural Research, 2019)
An experiment on an early indica rice cv. ‘Shenyou9576’ was conducted in the Key Laboratory of Phytohormones and Growth Development of Hunan Agricultural University, Changsha, Hunan, PR China in 2014 to investigate the influence of varying post-anthesis temperatures on chalkiness rate, head rice rate, and on major 6 starch synthesis enzymes i.e., SuSy (EC 1.9.3.1), ADPG-Ppas (EC 2.7.7.27), SSS (EC 2.4.1.21) and GBSS, (EC 2.4.1.21), SBE (EC 2.4.1.18) and SDBE (EC 3.2.1.70). The treatments comprised of three temperature regimes which are designated as the high (35/28oC- day/night), low (25/20oC- day/night) and natural condition (35/25oC-day/night) as the control. Under high temperature maximum chalkiness rate was 61.11% and minimum was 22.59% under low temperature treatment. The lowest head rice rate was 42.76% under high temperature treatment followed by 49.91% in the control, while the highest rate was 62.33% under low temperature treatment. Maximum grain filling rate (Gmax) was found highest (1.69 mg/day) in the high temperature and average grain filling rate (Gavg) was found highest (1.36 mg/day) under the control. The activity of SuSy, ADPG-Ppase, SSS and GBSS were decreased gradually from 14 to 35 days after flowering (DAF). Irrespective of the treatments, an increasing trend of ADPG-Ppase activity was observed from 7 to 14 DAF and then declined. Correlation between the chalkiness and the enzymes activity of SuSy, ADPG-Ppase and SSS were significantly negative at 21, 28 and 35 DAFs, i.e., higher activity of SuSy, ADPG-Ppase and SSS at the mid-late to the late caryopsis development stage mediated by low temperature treatment played an important role for the reduction of chalkiness. The correlation between GBSS activity and chalkiness was significantly negative and stronger at 14, 21 and 28 DAF indicating that GBSS played a cardinal role to reduce chalkiness in the mid to mid-late stage of rice grain development. Significantly negative correlation was found between starch branching enzyme (SBE) and chalkiness at 21, 28 and 35 DAF, i.e., the higher SBE activity under low temperature treatment at the later grain filling stage also had a positive role in reduction of chalkiness. Bangladesh J. Agril. Res. 44(2): 223-238, June 2019